- + 8х + 3х - 24 = -х (х - 3) + 8 (х - 3) = (х - 3) (8 - х)
- - 11х + 2х + 22 = -х (х + 11) + 2 (х + 11) = (х + 11) (2 - х)
- - 17х + 3х + 51 = -х (х + 17) + 3 (х + 17) = (х + 17) (3 - х)
-2 - 22х + 11х + 121 = -2х (х + 11) + 11 (х + 11) = (х + 11) (11 - 2х)
-4 + 10х - 12х +30 = -4х (х + 3) + 10 (х + 3) = (х + 3) (10 - 4х)
-5 - 10х + 4х + 8 = -5х (х + 2) + 4 (х + 2) = (х + 2) (4 - 5х)
4 + 16х - 5х - 20 = 4х (х + 4) - 5 (х + 4) = (х + 4) (4х - 5)
9 - 27х + 6х + 18 = 9х (х - 3) + 6 (х + 3)
В последнем, скорее всего, какая-то ошибка, потому что преобразовать его в произведение невозможно.
Решение: 1-sin2x=cosx-sinx (cosx-sinx)²=cosx-sinx (cosx-sinx)²-(cosx-sinx )=0 (cosx-sinx)(cosx-sinx-1)=0 a) cosx-sinx=0 1-tgx=0 tgx=1 x1=π/4+πn б) cosx-sinx-1=0 cos²(x/2)-sin²(x/2)-2sin(x/2)cos(x/2)-cos²(x/2)-sin²(x/2)=0 -2sin²(x/2)-2sin(x/2)cos(x/2)=0 2sin(x/2)(sin(x/2)-cos(x/2))=0 sin(x/2)=0 x/2=πn x2=2πn sin(x/2)-cos(x/2)=0 tg(x/2)=1 x/2=π/4+πn x3=π/2+2πn
Объяснение:
надеюсь